Contribution of controlling to business efficiency - Todorović - Dudić, Aleksandra; Stanišić, Mile; Perović, Veselin (Industrija, 2017)
The authors of the paper analyse the contribution of controlling to enterprise efficiency. Controlling is an approach that helps companies focus on creating value and driving value creation, quality increase and cost reduction. On the basis of a representative sample of industrial-sector companies in Serbia, the authors conducted a multivariate analysis of variance (MANOVA), discriminant analyses and other parametric procedures and methods. Univariate procedures applied are the Roy′s test, Pearson′s contingency coefficient (c) and the multiple correlation coefficient (R). As a result, the difference in controlling among enterprises relating to identification of controlling contribution to enterprise efficiency is determined. The existence of a boundary is confirmed. As a clear boundary between controlling processes in enterprises is defined, their characteristics are also determined.